The End of War in Papua New Guinea: "Crime" and "Tribal Warfare" in Post-Colonial States - Roscoe, Paul (Anthropologica, 2014)
The contemporary Pacific is a region of colonial and post-colonial states, the nature of which poses challenges to envisioning "the end of war." Although prevailing global discourses commonly equate post-colonial and nation states, differences in the evolutionary dynamics and histories of the two differ in ways that cast doubt on whether pre-colonial war ever really ended in many post-colonial polities and how easily it might be brought to an end. These issues are discussed with reference to "crime" and "tribal warfare" in contemporary Papua New Guinea.